GEOPHYSICAL INVESTIGATION OF POTENTIAL FELDSPAR DEPOSITS IN MOKWA, NIGERIA FOR ECONOMIC BENEFITS - Usman, Yusuf Tanko (FUDMA Journal of Sciences, 2020)
The geophysical technique of Electrical Resistivity in mineral rocks investigation has been found to be one of the very effective and convenient methods. It was therefore applied using Schlumberger configuration to investigate the location, depth and the economic viability of Feldspar mineral deposits at the study location in Mokwa, Niger State, Nigeria. This research is aimed at determining the location and economic viability of Feldspar deposits in Mokwa that can serve as Industrial fillers or induce the development and sustainability of both small and medium scale paint, plastic, rubber and adhesive Industries within and outside the study area. 30 Vertical Electrical Soundings (VES) were acquired in 6 profiles using ABEM SAS 4000 Terrameter with 50 m spacing in between each profiles. The results revealed that Profile 1 VES point 5, profile 2 VES point 2, profile 4 VES point 4 and profile 5 VES point 5 are underlined with rocks of Low electrical resistivity values which implied possible Feldspar deposits. The highest Feldspar Deposits with average thickness of 7.87 m was discovered in profile 1, while profile 4 exhibited the lowest deposits with thickness of 2.50 m. On the average, the depths of these minerals rocks from the surface fell in the interval of 0.06 m to 8.00 m. However, the discovered feldspar deposits are not of much economically viable for Industrial filler exploration capable of influencing any Industrial development in either small or medium scale capacity.
Keywords: Feldspar Deposits, Industrial filler, VES, Electrical Resistivity